Prospect of Circular RNA in Hepatocellular Carcinoma: A Novel Potential Biomarker and Therapeutic Target - Yao, Renzhi; Zou, Haifan; Liao, Weijia (Frontiers in Oncology, 2018)
CircRNA, a kind of tissue specific and covalently closed circular non-coding RNA is very abundant in eukaryocyte. Generally, circRNA is generated by back-splicing of protein-coding genes’ pre-mRNA. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world. Due to the characteristics of poor prognosis and high recurrence, the pathogenesis of HCC is highly concerned by researchers worldwide. Recent studies demonstrated that numerous circRNAs were differentially expressed in HCC tissues and normal liver tissues, which is closely related with the development and prognosis of HCC. However, the mechanism of circRNA in HCC remains unclear. In this review, we summarized the abnormal expressions of circRNAs in HCC, discussed its role and potential mechanisms, and tried to explore the prospective values of circRNA in the diagnosis, therapy and prognosis of HCC.